2020
DOI: 10.1186/s12958-020-00679-9
|View full text |Cite
|
Sign up to set email alerts
|

Genipin improves reproductive health problems caused by circadian disruption in male mice

Abstract: Background Circadian rhythm disruption impacts a wide range of physiological processes, including fertility. However, the effect of circadian disruption on male spermatogenesis and fertility, and treatments for these effects have been largely unexplored at the molecular level. Methods In this study, we examined the effects of genipin on improving the reproductive health problems caused by circadian disruption. Three groups of animals were fed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…An extract from Gardenia jasminoides Ellis, a genipin, reversed the adverse changes in spermatogenesis and fertility caused by photoperiod disturbance in male mice. A normalization of sex hormones and proteins involved in steroidogenesis was observed, as well as a reduction of atrophy of the seminiferous tubules, decreased vacuolization, and restoration of typical control animals' sperm motility and concentration [41].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…An extract from Gardenia jasminoides Ellis, a genipin, reversed the adverse changes in spermatogenesis and fertility caused by photoperiod disturbance in male mice. A normalization of sex hormones and proteins involved in steroidogenesis was observed, as well as a reduction of atrophy of the seminiferous tubules, decreased vacuolization, and restoration of typical control animals' sperm motility and concentration [41].…”
Section: Discussionmentioning
confidence: 79%
“…Although it is known that the desynchronization of endogenous circadian clocks affect each level of the HPG axis, the level of sex hormones, the process of spermatogenesis, final sperm concentration and motility, and, ultimately, fertility -both in males of various vertebrate species and in humans [8,39,40]. It has been shown that mice exposed to shortened light-dark cycle (Light/ Dark = 4 hours/4 hours) for 5 or 10 weeks responded with reduced testes size, abnormal morphology, decreased sperm concentration and motility, and lowered levels of dihydrotestosterone and androstenedione [41]. In our experiment, we found that 5-week exposure to both SD and LD photoperiods reduced sperm count and motility and increased the number of abnormal sperm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It also offers potential in biocatalyst design, particularly in food modifications [ 69 ]. The physicochemical characteristics of genipin-cross-linked hydrogels, as well as various information on the use of biomaterials for drug delivery, including ocular drug delivery, buccal drug delivery, anti-inflammatory drug delivery, oral drug delivery, are given in a recent review by Xu et al [ 70 ].…”
Section: Genipin As a Crosslinking Compoundmentioning
confidence: 99%